Analysis of Supporting Factors and the Role of Teachers in Stimulating Social Behavior of Children Aged 4-5 Years at PAUD KB Mekarsari Mataram (Jurnal Ilmu Pendidikan dan Sains: Visioedusains, 2026)
The development of social behavior is one of the important aspects of early childhood education that needs to be optimally stimulated from an early age. Teachers have a strategic role in shaping children's social behavior through various learning activities and interactions that take place in the school environment. However, children are still found who have difficulty interacting, cooperating, sharing, and showing empathy for peers. This study aims to describe the role of teachers in stimulating the social behavior of children aged 4–5 years and identify the factors that affect the development of children's social behavior in PAUD KB Mekar Sari Mataram. This study uses a qualitative approach with a descriptive type of research. The research subjects consisted of school principals, classroom teachers, and children aged 4–5 years. Data collection techniques are carried out through observation, interviews, and documentation, while data analysis uses the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawn. The results of the study show that teachers have carried out their roles well as educators, motivators, managers, supervisors, innovators, and communicators in stimulating children's social behavior. Stimulation is carried out through example, habituation, playing together, group work, and providing motivation and positive reinforcement. Developed social behaviors include friendliness, cooperation, sharing, sympathy, and discipline. In addition, family factors and the school environment are the main factors that affect the development of children's social behavior.